PENGARUH MATERIAL INTI BESI TERHADAP NILAI BACK-EMF DAN KE PADA PERMANENT MAGNET SYNCHRONOUS GENERATOR 12S8P MENGGUNAKAN SOFTWARE BERBASIS FINITE ELEMENT METHOD - Iqbal Fadillah, Muhammad; Abdi Bangsa, Insani (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2022)
The iron core is a major component in the generator, of course also in the Permanent Magnet Synchronous Generator (PMSG). In this journal we will vary the iron core, there are two iron cores, namely the rotor and the stator. Varying this iron core by replacing the material on the stator and rotor with a rotor, stator and rotor-stator scheme. By varying the material in the iron core, we will analyze, then conclude the Back-EMF value and KE value. The essence of this journal is to vary the iron core material on the Permanent Magnet Synchronous Generator (PMSG) 12S8P so as to obtain BACK-MF and KE values. Keywords: Generator, PMSG, Iron Core